Environmental pollution risk and insurance - Vito Fragnelli; Maria Erminia Marina (Fondazione Eni Enrico Mattei (FEEM), 2002)
We consider environmental risks that are evaluated too much heavy for a single insurance company, but they can be insured by n companies which a premium is assigned to.This is precisely the Italian scenario where a pool of companies co-insures these risks.Under a game theoretic approach we start by analyzing how they should split the risk and the premium in order to be better off. Under suitable hypotheses, there exists an optimal decomposition of the risk, that allow us to define a cooperative game whose properties and some particular solutions are analysed.
Keywords: 330; Environmental risk; Cooperative game; Umweltbelastung; Risikomodell; Versicherung; Spieltheorie; Theorie; Italien